Effect of Environment on Heartwood Amount in Dalbergia sissoo Roxb. in Different Climatic Zones of Punjab - Rishi, L. B.; Sidhu, D. S. (Indian Forester, 2002)
Dalbergia sissoo , commercially known as Sissoo is considered as one of the best timbers in India. Durable under both exposed and indoor conditions , heartwood is rarely attacked by borers and White ant. As sapwood is very much prone to borer attack , logs having higher heartwood amount fetch much higher price in the market. The present study was undertaken to find out the variation in heartwood amount in Dalbergia sissoo in different zones of Punjab. The study was conducted in three broad agro-climatic zones , viz. , Kandi zone , Central plain zone , and South-western dry zone of Punjab. 79.36 percent heartwood was recorded for Kandi zone which was significantly higher than the other two zones , viz. , Central plain zone (76.02%) and South-western zone (76.89%). There was no significant difference in heartwood amount in localities within each of these zones. Heartwood thickness had strong linear relationship with the total diameter in all the three zones and regression equation was worked out to predict the amount of heartwood in D. sissoo from the diameter of the tree.